Studi Teacher's Burnout Dalam Pelaksanaan Undang-Undang Guru Dan Dosen Mengenai Beban Kerja Guruakuntansi di SMK Negeri 1 Karanganyar - Putri, Nur Kusuma, Muhammad Fahmi Johan Syah, M.Pd (2017)
This study aims to determine (1) Indications that can be included in the criteria of a person experiencing burnout, (2) Application or implementation of Teachers and Lecturers Law regarding teacher workload. This research uses qualitative method. Data collection techniques used in research are interviews, observation and documentation. The resource persons who became the object in the study are four accounting teachers. Design research in this research using phenomenology approach. The validity of data in this study is measured through data triangulation. Data analysis techniques used are data reduction, data display and conclusion drawing / verification Based on the results of the study, teachers who experience burnout showed characteristics such as emotional fatigue, sisism and energy loss accompanied by fatigue. Burnout teachers are teachers who have higher levels of time pressure in their work than with other teachers. Teachers who did not experience burnout showed no symptoms or traits as was the case with teachers who experienced burnout.